Pengelolaan Arsip Dinamis pada Kantor Kelurahan Mangga Kecamatan Medan Tuntungan Kota Medan - Risky, Putri Ayu Risky; Mohamad Firdaus (MIZANIA: Jurnal Ekonomi Dan Akuntansi, 2024)
Dynamic Archives are important documents used directly in administrative activities and public services. This study was conducted to examine how dynamic archive management is carried out at the Mangga Sub-district Office, Mangga Tuntungan District, Medan City. The research method used is a qualitative approach with data collection techniques including interviews with relevant sources, direct observation, and document studies. The results of the study show that data management is still done manually. The archive management stages creation, administration, usage, maintenance, and final disposition have been implemented, but not optimally. Several obstacles were identified, such as unsystematic archive arrangement, lack of knowledge and skills among staff in managing archives, and inadequate infrastructure. To overcome these challenges, strategies such as developing standard operating procedures (SOPs), conducting archival training, and providing facilities to support archive digitization have been implemented. By applying these strategies, it is expected that archive management can be carried out more effectively and efficiently to support optimal public service delivery.